Realisasi Alat Ukur Suhu Dan Kelembapan Berbasis Raspberry Pi - Septian angga pratama; Nana Subarna (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2019)
AbstractTemperature and humidity are one of the most frequently measured parameters. Measurements of temperature and humidity parameters are very useful for studying a physical, chemical, or biological process. In the last few decades, global warming or global warming has become a global issue related to the environment where pollution and damage to the environment are factors that cause high temperatures in the earth. Therefore the main focus of this research is about measuring the temperature and humidity of a room with a dimension of 15 x 10 m whether it is necessary to have additional cooling in the room or not to know the level and level of linearity of the DHT 11 sensor that will be used to measure two parameters at once, with a microcontroller in the form of a Raspberry Pi. Measurements were made by taking 30 samples for 30 minutes, the results displayed from the monitor connected from Raspberry Pi showed that the DHT 11 sensor was not linear, namely the temperature R2 = 0.8221, while the humidity R2 = 0.8893 was due to the influence of temperature from outside and indoors and the influence of the quantity of humans in the room. Keywords : DHT11, Raspberry Pi, Room, Temperature and Humidity